The effect of white noise on sucking success and infant comfort in premature babies: a paired randomized controlled trial - Esra Tanrıverdi; Tülay Kuzlu Ayyıldız (Journal of Pediatric and Neonatal Individualized Medicine, 2023)
Purpose: This study was conducted in a paired randomized controlled trial manner to determine the effect of white noise on sucking success and infant comfort in premature babies.